Challenging the status quo - car ownership and the Generation Y: An analysis of the German market - Wesselmann, Jonas (2018)
Purpose – This work aims to identify how people of the Generation Y in Germany see the future of mobility with a special focus on car ownership. Furthermore, determinants influencing car ownership are analyzed and implications for the automotive industry are drawn. Design/Methodology – The research relies on primary data collected through an online survey among 20 – 27 years old people in Germany. In order to draw valid conclusions, the data was analyzed carrying out logistic regressions. Findings – Two main factors that influence the likelihood if people own a car were identified. Living in rural areas and being employed are positively associated with car possession, while no significant relationship between environmental attitude and car ownership could be identified. Research limitations – The older part of the Generation Y, those above 27 years, was not covered by the data, therefore no general conclusions on the behavior of the whole generation and international differences can be drawn. Practical implications – This research can help corporations in the automotive and mobility industries to further understand and differentiate their target segment. People of the Generation Y cannot be seen as one homogenous group but need to be identified as fragmented subgroups with entirely different needs and desires. Originality – To the knowledge of the author, this is the first study that combines the topics of Generation Y and sharing economy with the trends in the automotive industry to identify peoples’ perception of mobility.